Mecanismos de abertura do sulco e da adubação nitrogenada em arroz de terras altas - Nascimento, Vagner Do (2013)
The rice crop has poor adaptation to the no till (NT) system because of the higher topsoil compression caused by the intense machine trafficking and reduced tillage operations. In this case, the implement used for opening furrows for fertilizer application is important to facilitate the root penetration and increase soil porosity. This study evaluated the performance and yield of upland rice in no till system as a function of the implements used for fertilizer application at sowing and N rates in Selvíria (MS), Brazil. The experiment was arranged in a randomized block design, using a 2 x 6 factorial arrangement, consisting of two fertilizer distribution implements (chisel plow and double disc plough) and six rates of topdress nitrogen (0, 25, 50, 75, 100 and 125 kg ha-1) with four replicates. The implements of fertilizer application did not affect the rice yield. The chisel plow provided higher plant height and number of filled grains in the two years of cultivation. The topdress nitrogen application affected some agronomic characteristics, production and milling yield components; the rice yield increased up to of the rate 69 kg ha-1 of N, in the first crop year.